Assessment of Bioactive Compounds under Simulated Gastrointestinal Digestion of Bee Pollen and Bee Bread: Bioaccessibility and Antioxidant Activity - Volkan Aylanc; Andreia Tomás; Paulo Russo-Almeida; Soraia I. Falcão; Miguel Vilas-Boas (MDPI AG, 2021)
Bee pollen and bee bread have always been regarded as excellent natural resources for application in food and pharmaceutical fields due to their rich nutrient content and diversity of bioactive compounds with health-improving properties. Extensive studies on both bee products as ingredients for a healthy diet were reported, although the data concerning their metabolization on the gastrointestinal tract is quite limited. Here, we report, at each digestive stage, the bioactive profile for both bee products, their bioaccessibility levels and the antioxidant activity evaluation. The findings indicated that the average bioaccessibility level of total phenolic and total flavonoid content for bee pollen was 31% and 25%, respectively, while it was 38% and 35% for bee bread. This was reflected in a decrease of their antioxidant capacity at the end of in vitro gastrointestinal digestion, both in free radicals scavenging capacity and in reducing power. Moreover, within the 35 phytochemicals identified, the most affected by gastrointestinal digestion were phenylamides, with a complete digestibility at the end of the intestinal phase. Overall, our results highlight that bioactive compounds in both raw products do not reflect the real amount absorbed in the intestine, being bee bread more accessible in bioactive content than bee pollen.